2018
DOI: 10.5114/jos.2018.83405
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cognitive functioning as an effect of complex treatment of myofascial pain in temporomandibular disorders

Abstract: Introduction: Pain reduction is a benefit that comprehensive treatment of myalgic temporomandibular disorders can provide. Myalgic pain reduction is associated with a series of changes at the neurophysiological level, which are inseparably connected with psychoemotional and cognitive changes. It has not been established if the course of these changes is the same for chronic myofascial pain in temporomanibular disorders as it is for other types of chronic pain. Objectives: The present study examined changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that guided meditation reduce complication and improve sleep quality of patients with fractures [23] and another study also showed that relaxation technique can reduce fatigue and improve sleep quality in patients with COPD. The reason for the decrease in anxiety of patients after guided meditation training may be attributed to the balance between the anterior and hypothalamic nucleus, which reduces the activity of the sympathetic nervous system and prevents side effects of stress and anxiety and lead to physical and mental relaxation [24].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that guided meditation reduce complication and improve sleep quality of patients with fractures [23] and another study also showed that relaxation technique can reduce fatigue and improve sleep quality in patients with COPD. The reason for the decrease in anxiety of patients after guided meditation training may be attributed to the balance between the anterior and hypothalamic nucleus, which reduces the activity of the sympathetic nervous system and prevents side effects of stress and anxiety and lead to physical and mental relaxation [24].…”
Section: Discussionmentioning
confidence: 99%